2011
DOI: 10.1007/s13149-011-0136-6
|View full text |Cite
|
Sign up to set email alerts
|

Le béribéri, maladie nutritionnelle récurrente en milieu carcéral en Côte-d’Ivoire

Abstract: As a re-emerging disease, beriberi caused by a lack of thiamine in food threatens more and more prisons in developing countries. Indeed in 2008, a beriberi epidemic occurred in a detention house of Côte-d'Ivoire called Maca. The goal of our retrospective investigation was to describe this epidemic in order to improve prisoners' health. The study related to 131 subjects, 64% of cases affected (N = 205). The total rate of beriberi attack was estimated at 38.6‰. The mean age was 33; all patients were male and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…However, malnutrition could also be a risk factor for increased risk of infections [3537] and may be an important indicator of prognosis from infectious diseases of the respiratory system [38, 39]. Additionally, multiple other studies have also demonstrated that prisoners were suffering from several micronutrient deficiencies that could predispose them to severe forms of infections in addition to other health problems such as depression and mortality [911, 14, 19, 4044]. In our study, 9% of the prisoners were either severely or moderately underweight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, malnutrition could also be a risk factor for increased risk of infections [3537] and may be an important indicator of prognosis from infectious diseases of the respiratory system [38, 39]. Additionally, multiple other studies have also demonstrated that prisoners were suffering from several micronutrient deficiencies that could predispose them to severe forms of infections in addition to other health problems such as depression and mortality [911, 14, 19, 4044]. In our study, 9% of the prisoners were either severely or moderately underweight.…”
Section: Discussionmentioning
confidence: 99%
“…The literature indicates that prisoners face different nutritional problems ranging from several micronutrient deficiencies, re-emerging severe diet related diseases to delayed recovery, mental illness, sexual health problems, infectious diseases, a wide range of risk factors and increased risk of mortality [6, 7, 920]. …”
Section: Introductionmentioning
confidence: 99%
“…From a clinical eye examination, the nutrition related diseases xerophthalmia and optic neuropathy were identified. Elsewhere, severe malnutrition has been documented in prisoners in Zimbabwe [41], Democratic Republic of Congo, as well as vitamin A deficiency in Kenya [2] and beriberi in the Cote d’Ivoire [3,42]. Clearly, ongoing vigilance of prisoners’ diets is required.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, thiamine deficiency outbreaks were described among young healthy Thai construction workers in Singapore in the 1980s [ 8 , 9 ] and among commercial fishermen in Thailand in 2005 [ 10 , 11 ]. Worldwide, outbreaks of thiamine deficiency have recently been reported in Ivory Cost jails [ 10 , 12 ], in the Gambia [ 13 , 14 ], among African Union troops in Mogadishu, Somalia [ 15 ], in Brazil [ 15 18 ] and the French island of Mayotte [ 19 ]. Adult thiamine deficiency was also recently described in Cambodia, China, India, Thailand, Laos and various countries with unbalanced thiamine/thiaminase diets [ 8 , 19 – 24 ].…”
Section: Introductionmentioning
confidence: 99%